PENGEMBANGAN MODUL AJAR PENDAHULUAN VEKTOR TERKAIT KEMAMPUAN BERPIKIR KREATIF MATEMATIS BERBASIS PROBLEM-BASED LEARNING - Ismail Taufik Hidayah; Yayu Laila Sulastri; Luki Luqmanul Hakim (Universitas Islam Nusantara, 2022)
This research was motivated by the change of the minister of education so that it had an impact on the use of the curriculum in education units where the new curriculum that emerged at this time was the independent curriculum. Where in this independent curriculum, the learning tools used by educators have many changes, one of which is the RPP in the independent curriculum being changed into Teaching Modules. Then the low creative thinking ability of students and the lack of understanding of students on vector introduction material so that the development of vector introduction material teaching modules is needed. The purpose of this study is to determine the level of validity, effectiveness and practicality of the development of teaching modules. The research method used is Design-based Research (DbR) with the Plomp model. The data sources in this study are material expert validators, media experts, and respondents. The instruments used in this research are material and media expert validation sheets as well as effectiveness and practicality questionnaires. The data obtained were analyzed using percentages which were interpreted according to their qualifications. Based on the results of the analysis carried out, it can be concluded that the development of teaching modules developed is valid, effective, and practical as well as the implementation of linkages with creative thinking skills in the complete category, and student responses meet positive criteria. It is recommended that further research be carried out on a large scale or using other mathematical abilities.